Progressive Multifocal Liquid Lenses Based on Asymmetric Freeform Surface Structure of Nonuniform Thickness Elastic Membranes with Different Constraints - Weiliang Jia; Biao Zhang; Songjing Li (International Journal of Optics)
For a progressive multifocal liquid lens with an elastic membrane deformed by liquid pressure, to realize a reasonably power distribution, asymmetric deformation characteristics of the membrane surface are needed. Based on the asymmetric freeform surface structure, this paper proposed progressive multifocal liquid lenses focused by liquid with nonuniform thickness membranes. The structure and mathematical model of power distribution for the lens are introduced. The membrane deformation and the corresponding power distribution of the lenses with asymmetric freeform surface are predicted and compared under uniform pressure load and different boundary conditions using the finite element method. An optical testing system is constructed to analyze the optical characteristics of the fabricated lenses through observing the focusing performance of the F target image at different regions of the lenses. Experimental results show that the liquid lenses can realize as asymmetrical progressive multifocal liquid lenses after liquid accommodation; meanwhile, the trends of power distribution of the lenses generally agree well with simulations.